pjdole An Investigation of AIOU Students’ Satisfaction About Formative M-Assessment Using SMS Technology: Kamran Mir , Muhammad Zafar Iqbal , Jahan Ara Shams (PJDOL, 2023)
Open and Distance Learning (ODL) plays an important role in providing education to the students of rural and remote areas. In ODL, learning feedback and assessment process of learners requires time and cost using classical communication techniques. Emerging technologies like Mobile Assessment (M-Assessment) has gained momentum because of its potential as a useful electronic assessment tool available on widely used mobile devices. The mobile phone usage in Pakistan over the last ten years has been increased incredibly but the potential of Short Messaging Service (SMS) technology in assessment activity has not been fully explored. This study focuses on mobile SMS usage for formative assessment in distance learning environment of Allama Iqbal Open University (AIOU).